THE CHARACTERISTICS OF PRIMITIVISM IN ERNEST HEMINGWAY’S THE OLD MAN AND THE SEA - Santosa, Vyrna (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Authors of any periods unconsciously tend to explore the sublimity and free expression of feeling, the simplicity of style and themes, the portrayal of the ’noble savage’, the glorification of nature, the excitement of physical power and sensuous use of language. These are the characteristics of primitivism, the celebration of an earlier stage of human development, which is uncorrupted, vigorous, genuine expression of life. Ernest Hemingway’s The Old Man and the Sea clearly depicts the characteristics of primitivism as seen in the portrayal of its main character, Santiago. Hemingway’s regret on the impact of technology led him to write the novella with its hero who is depicted with the qualities of being a true hero, a winner ’who takes nothing’ ; a ’noble savage’ with great courage of physical action while dealing with nature. Santiago has become the portrayal of Hemingway’s criticism toward the development of civilization and the urban way of life.